2012
DOI: 10.1111/mec.12125
|View full text |Cite
|
Sign up to set email alerts
|

Outlier loci highlight the direction of introgression in oaks

Abstract: Loci considered to be under selection are generally avoided in attempts to infer past demographic processes as they do not fit neutral model assumptions. However, opportunities to better reconstruct some aspects of past demography might thus be missed. Here we examined genetic differentiation between two sympatric European oak species with contrasting ecological dynamics (Quercus robur and Quercus petraea) with both outlier (i.e. loci possibly affected by divergent selection between species or by hitchhiking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 80 publications
16
103
0
Order By: Relevance
“…Bodénès et al 2016, see Table 1). Leaves were sampled, stored in silica gel and sent to INRA (Cestas, France) for DNA extraction following Guichoux et al (2013). DNA quality and concentration were assessed with a Nanodrop spectrophotometer (NanoDrop Technologies,Wilmington,152 DE,USA) and by separating samples in 1% agarose gels stained with ethidium bromide.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Bodénès et al 2016, see Table 1). Leaves were sampled, stored in silica gel and sent to INRA (Cestas, France) for DNA extraction following Guichoux et al (2013). DNA quality and concentration were assessed with a Nanodrop spectrophotometer (NanoDrop Technologies,Wilmington,152 DE,USA) and by separating samples in 1% agarose gels stained with ethidium bromide.…”
Section: Sample Collectionmentioning
confidence: 99%
“…That percentage corresponds to the mean admixture from second-generation backcrosses (BC2); it is large enough to avoid statistical noise (mean admixture in BC3 would be 6.25%), and has been previously used to identify pure species among hybridizing oaks (Goicoechea et al, 2012;Guichoux et al, 2013).…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 99%
“…Although restricting the study to SNPs derived only from coding regions may have overestimated the proportion of outlier loci to some extent, outlier detection studies in other tree species revealed similar proportions of outliers at a large scale (4400 km), for example in Picea glauca (5.5% outliers, F ST = 0.006, genic SNPs) (Namroud et al, 2008), A. glutinosa (3.7% outliers, F ST = 0.057, amplified fragment length polymorphisms; and 2.86%, F ST = 0.01, SNPs) (Cox et al, 2011;De Kort et al, 2014), and Quercus robur and Q. petraea (4% and 5% outliers resp., F ST = 0.013 and 0.015 resp., genic SNPs) (Guichoux et al, 2013). Nevertheless, many of these findings should be interpreted with considerable caution due to the use of candidate loci (except for those of Cox et al, 2011, De Kort et al, 2014, which tend to overestimate neutral distributions and therefore underestimate the true percentage of loci under selection, the latter being expected to be high when using loci related to adaptive functions or traits.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, a standard Bayesian population genomic outlier screen (BAYESCAN, Foll & Gaggiotti, 2008) was complemented with individual-based latent factor mixed modeling (LFMM, Frichot et al, 2013), and multivariate redundancy analyses (RDA, Borcard et al, 2011), to identify (i) SNPs putatively under selection and (ii) the main environmental drivers of population differentiation while accounting for spatial autocorrelation in allele frequencies. Although the use of candidate SNPs has been the standard method to find loci putatively under selection (for example, Namroud et al, 2008;Alberto et al, 2013;Guichoux et al, 2013;Olson et al, 2013), they may compromise the relevance of classical outlier detection methods due to overestimation of neutral distributions. This stresses the importance of integrating landscape genomic methods to reliably reveal loci putatively under selection and the selective agents underlying the observed patterns (De Villemereuil et al, 2014;Weinig et al, 2014).…”
Section: Introductionmentioning
confidence: 99%